Advanced Quantum Mechanics - Schwabl, Franz (Springer Berlin Heidelberg : Imprint: Springer, 2005)
Advanced Quantum Mechanics, the second volume on quantum mechanics by Franz Schwabl, discusses nonrelativistic multi-particle systems, relativistic wave equations and relativistic fields. Characteristic of Schwabl's work, this volume features a compelling mathematical presentation in which all intermediate steps are derived and where numerous examples for application and exercises help the reader to gain a thorough working knowledge of the subject. The treatment of relativistic wave equations and their symmetries and the fundamentals of quantum field theory lay the foundations for advanced studies in solid-state physics, nuclear and elementary particle physics. This text extends and complements Schwabl's introductory Quantum Mechanics, which covers nonrelativistic quantum mechanics and offers a short treatment of the quantization of the radiation field. New material has been added to this third edition of Advanced Quantum Mechanics on Bose gases, the Lorentz covariance of the Dirac equation, and the 'hole theory' in the chapter "Physical Interpretation of the Solutions to the Dirac Equation.".